Shahids and martyrs: Conflicting national narratives and places of memory in Kosovo - Péter Reményi; Nurcan Özgür Baklacioğlu; Norbert Pap (Hungarian Geographical Bulletin, 2024)
Kosovo Field (Kosovo Polje), the core region of the newly independent Kosovo, experienced several key historical events, each of which left important memories in the space. As political control over territory changed, different memories connected to the area became stronger, while others were pushed into the background. The first battle of Kosovo (1389) and the death of their ruler Lazar, is a key event in Serbian history, identified through spectacular landmarks in the region. Connected to this event, Turkish monuments also exist, commemorating the death of the martyr Sultan Murad I. Following independence, memorials of Albanian fighters started mushrooming as a core element of Kosovar identity building, with the martyrdom of the “legendary commander” Adem Jashari being central to this emblematic memory project. All three nations have an “official” martyr connected to the space, around which different nation-building narratives have been constructed. As the struggle over the control and influence of the region continues, so does the competition of different memories and memorials. Territorialisation and de-territorialisation of memories are ongoing projects in the country by the three nations, linked to competing nation-buildings and political power struggles.